2022
DOI: 10.1186/s12905-022-01980-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Iraqi people’s perception about early marriage: a qualitative study

Abstract: Background and objective Early marriage is prevalent in Iraq, but the factors related to this behavior, especially people's attitudes about it, have not been well studied. It has been proven that early marriage seriously threatens young girls' lives and health. This study aimed to explore the perception of people about early marriage in the Iraqi Kurdistan region. Methods A qualitative method was employed to carry out this study in 2020. Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…These factors contribute to the breakdown of relationships and can lead to irreconcilable differences between spouses. Research shows that those who marry early lack knowledge of marital roles, and this unconsciousness leads to a lack of intimacy and, consequently, marital instability [20,21]. Additionally, young couples often lack essential communication, problem solving, and con ict resolution skills, which are crucial for navigating the complexities of married life and reducing the likelihood of divorce.…”
Section: Discussionmentioning
confidence: 99%
“…These factors contribute to the breakdown of relationships and can lead to irreconcilable differences between spouses. Research shows that those who marry early lack knowledge of marital roles, and this unconsciousness leads to a lack of intimacy and, consequently, marital instability [20,21]. Additionally, young couples often lack essential communication, problem solving, and con ict resolution skills, which are crucial for navigating the complexities of married life and reducing the likelihood of divorce.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified a personal and family history of mood disorders, marital conflict, younger age, limited social support, and a higher number of children as risk factors for depression during pregnancy . Substance abuse has also been found to be significantly associated with antenatal depression [6,7] . The rationale for this study is based on several factors.…”
Section: Introductionmentioning
confidence: 99%